2020
DOI: 10.1038/s41433-020-01240-z
|View full text |Cite
|
Sign up to set email alerts
|

A virtual-clinic pathway for patients referred from a national diabetes eye screening programme reduces service demands whilst maintaining quality of care

Abstract: Aim To evaluate the potential of an integrated virtual medical retina clinic in secondary care for diabetic patients screened and referred by the UK National Diabetic Eye Screening Program (DESP). Methods This retrospective cohort study included diabetic patients referred by the DESP to either a virtual or a traditional doctor’s appointment (face-to-face, F2F) at the Moorfields Eye Hospital NHS Foundation Trust (London, UK) between January 2015 and December 2018. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“… 14 Faes et al reported a DNA rate of 32% and 28% from DRS to HES, for face to face, and virtual consultations, respectively. 15 Keenum et al found that 24% of patients referred with STDR had no record of attendance at the ophthalmology service two years after initial referral. 16 …”
Section: Discussionmentioning
confidence: 99%
“… 14 Faes et al reported a DNA rate of 32% and 28% from DRS to HES, for face to face, and virtual consultations, respectively. 15 Keenum et al found that 24% of patients referred with STDR had no record of attendance at the ophthalmology service two years after initial referral. 16 …”
Section: Discussionmentioning
confidence: 99%
“…One of the major limitations of telemedicine in retina is the need to obtain anatomical evaluation of the macular and retina to make treatment decisions. Prepandemic, various institutions have already developed imaging-based “virtual” clinics, with asynchronous review of imaging results and telemedicine-based communication of findings to patients 7–9. These virtual imaging clinics often deploy optical coherence tomography (OCT) with standard or ultra-widefield fundus photography to provide the imaging input required to manage diseases from diabetic retinopathy and macular edema to age-related macular degeneration (AMD).…”
Section: Methodsmentioning
confidence: 99%
“…Prepandemic, various institutions have already developed imaging-based "virtual" clinics, with asynchronous review of imaging results and telemedicine-based communication of findings to patients. [7][8][9] These virtual imaging clinics often deploy optical coherence tomography (OCT) with standard or ultra-widefield fundus photography to provide the imaging input required to manage diseases from diabetic retinopathy and macular edema to agerelated macular degeneration (AMD). Although these imaging clinics still require the patient to travel out of their homes for imaging, it has the potential to reduce crowding and waiting times in hospitals thereby improving social distancing and reducing the risk of infection.…”
Section: Retina and Ocular Imaging-based Models Of Care During Covid-19mentioning
confidence: 99%
“…Image analysis can also be performed by specially trained non-medical professionals, supported by automated image analysis outside the hospital in a reading centre. Reading centres and other specialists with the help of retina experts are the ones who currently develop AI based systems which should be able to decide if there is disease activity and make treatment suggestions, e.g., treatment intervals [ 10 , 14 , 21 , 36 38 ]. In the UK, a national system organized in this way to detect diabetics with retinal diseases requiring treatment has led to a marked reduction in legal blindness and an improvement in care without the need to increase medical staff [ 19 ].…”
Section: Relief From Physician-centred Care Structuresmentioning
confidence: 99%